2010
DOI: 10.1016/j.jcmg.2010.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Increased Pericardial Fat Volume Measured From Noncontrast CT Predicts Myocardial Ischemia by SPECT

Abstract: OBJECTIVES We evaluated the association between pericardial fat and myocardial ischemia for risk stratification. BACK GROUND Pericardial fat volume (PFV) and thoracic fat volume (TFV) measured from noncontrast computed tomography (CT) performed for calculating coronary calcium score (CCS) are associated with increased CCS and risk for major adverse cardiovascular events. METHODS From a cohort of 1,777 consecutive patients without previously known coronary artery disease (CAD) with noncontrast CT performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(96 citation statements)
references
References 39 publications
5
87
2
2
Order By: Relevance
“…Furthermore, perivascular fat was much more proinflammatory than fat from other sources and showed greatly increased release of TNF-␣, MCP-1 (CCL2), and MIP-1␣ (CCL3) upon high-fat feeding (1135). These findings provide new impetus for controlling weight gain and other factors that may increase deposition of coronary perivascular fat, recently shown to be strongly associated with atherosclerotic plaques in humans (1114,1161,1750).…”
Section: Vaso-vasorummentioning
confidence: 73%
“…Furthermore, perivascular fat was much more proinflammatory than fat from other sources and showed greatly increased release of TNF-␣, MCP-1 (CCL2), and MIP-1␣ (CCL3) upon high-fat feeding (1135). These findings provide new impetus for controlling weight gain and other factors that may increase deposition of coronary perivascular fat, recently shown to be strongly associated with atherosclerotic plaques in humans (1114,1161,1750).…”
Section: Vaso-vasorummentioning
confidence: 73%
“…15,17,18 Patients without chest pain who present with major adverse cardiovascular events have a bigger epicardial fat volume compared to event-free patients. 19 The coronary artery calcium score, a marker of CAD severity, has a positive correlation with EAT in patients with both obstructive and non-obstructive…”
Section: And Acute Coronary Syndromesmentioning
confidence: 97%
“…6,19 High PAT volume showed a positive correlation with a high level of high-sensitivity C-reactive protein and low level of adiponectin in one study, although a difference in the inflammatory marker could not be demonstrated between the two groups. 14,20 AVAT represents central obesity and is more powerful risk factor for CAD than ASAT.…”
Section: 18mentioning
confidence: 87%